Balance Training as an Adjunct to Methylphenidate: A Randomized Controlled Pilot Study of Behavioral Improvement Among Children With ADHD in China - Lei Feng; Lei Feng; Lei Feng; Yuanchun Ren; Jia Cheng; Jia Cheng; Yufeng Wang; Yufeng Wang (Frontiers in Psychiatry, 2021)
Objective: This study aimed to compare the therapeutic effects of two different approaches to attention deficit hyperactivity disorder (ADHD): (1) methylphenidate (MPH) treatment combined with balance training, and (2) MPH monotherapy.Methods: The study was based on a randomized, single-blind trial involving 27 ADHD patients. An experimental group received the treatment combining MPH and balance training, while a control group were administered just MPH. After 40 sessions of training at the 6-month mark, patients' improvement as observed in their core symptoms and behavioral problems were compared between the experimental and control group.Results: A total of 27 patients underwent randomization, with 13 assigned to the experimental group and 14 to the control group. After the 6-month trial, the experimental group outperformed the control group in terms of teachers' scores for inattention on the ADHD-RS-IV (19.38 ± 2.96 vs. 23.21 ± 3.91, t = −2.854, P = 0.009). The experimental group also showed greater improvement on the items involving behavior (3.14 ± 1.46 vs. 5.24 ± 1.04, t = 1.463, P = 0.026) and hyperactivity (1.92 ± 1.19 vs. 3.86 ± 2.32, t = −2.697, P = 0.012).Conclusion: In children with ADHD, the experimental group displayed a significant improvement in the symptoms and behavior associated with inattention than did the group whose treatment consisted of only MPH.